Multimedia development to improve character analysis thinking skills through value-based learning approaches - Arifin Arifin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research aims to develop interactive multimedia that can improve the quality of education, especially in strengthening students' character and personality, both holistically and comprehensively, according to the expectations of Indonesia's applicable curriculum. Qualitative methods are used in this study to get a complete picture to determine the developed multimedia response. The subjects of this study were one principal, two teachers, and five students. The instruments used in this study were in-depth interviews, observation, and documentation of the learning process using the developed multimedia. The results showed that students, in general, can use this multimedia in the learning process. There needs to be elaboration with teachers in different disciplines to present the material's depth according to the lessons. This research is recommended to all related parties who contribute to the development of students' quality following graduate standards' demands. In turn, it will produce a generation that is ready to enter a new era of knowledge, a better understanding of resources and factors that can affect both directly or indirectly, and it should be the basis for all related components and policymakers.